Testicular Cancer in New Zealand (TCNZ) study: protocol for a national case–control study. Issue 8 (5th August 2018) - Gurney, Jason K; Stanley, James; McGlynn, Katherine; Richiardi, Lorenzo; Shaw, Caroline; Edwards, Richard; Merriman, Tony R; Robson, Bridget; Koea, Jonathan; McLeod, Melissa; Kennedy, Martin A; Sarfati, Diana
Abstract : Testicular cancer (TC) is by far the most common cancer to affect young men; however, the exposures that cause this disease are still poorly understood. Our own research has shown that Māori men have the highest rates of this disease in New Zealand—a puzzling observation, since internationally TC is most commonly a disease of men of European ancestry. These trends provide us with a unique opportunity: to learn more about the currently unknown exposures that cause TC, and to explain why Māori have the highest rates of this disease in New Zealand. Using epidemiology and genetics, our experienced research team will conduct a nationwide study which aims to answer these internationally important questions. Aim of study: The overall aim of the current national case–control study is to identify the key exposures in the development of TC in New Zealand, and explore which factors might explain the difference in the incidence of TC between Māori and non-Māori. Methods and analysis: Outside of our own investigations into cryptorchidism, we still do not know which exposures are driving the significant incidence disparity between ethnic groups in NZ. The aim of the proposed research is to use a population-based case–control study to identify the key exposures in the development of TC in New Zealand. We will recruit 410 TC cases and 410 controls, and collect (1) environmental exposure data, via interview and (2) genetic information, via genome-wide genotyping. Ethics and dissemination: Ethical approval for this study was sought and received from the New Zealand Ministry of Health's Health and Disability Ethics Committee (reference # 17/NTA/248). Following a careful data interpretation process, we will disseminate the findings of this study to a wide and varied audience ranging from general academia, community groups and clinical settings, as well as to the participants themselves.